Complexities in the palaeoenvironmental and archaeological interpretation of isotopic analyses of the Mud Shell Geloina erosa (Lightfoot, 1786). (April 2017) - Twaddle, Robin W.; Wurster, Christopher M.; Bird, Michael I.; Ulm, Sean
Abstract: Isotope signals derived from molluscan shell carbonates allow researchers to investigate palaeoenvironments and the timing and periodicity of depositional events. However, it cannot be assumed that all molluscan taxa provide equally useful data owing to species-specific biological and ecological traits. The Mud Shell, Geloina erosa (Lightfoot, 1786) (syn. Polymesoda coaxans, syn. Polymesoda erosa ), an infaunal mangrove bivalve, is a common component of archaeological deposits along Australia's tropical north coast and throughout the Indo-West Pacific. The ubiquity of G. erosa has led to numerous researchers incorporating this taxon into interpretations of associated deposits, particularly in the generation of radiocarbon chronologies and as a palaeoenvironmental proxy. Despite this, concerns have been expressed regarding the impact of G. erosa physiology and ecology on associated geochemical signals. Adaptations allowing the survival of this species within its highly changeable mangrove environment may introduce complexities into radiocarbon and environmental data archived within its shell. This study combines local environmental and hydrological data with isotopic analysis (δ 18 O, δ 13 C, and 14 C) of live-collected specimens to explore the interpretability of geochemical proxies derived from G. erosa . Results suggest a number of factors may impact geochemical markers in unpredictable ways, eroding the usefulness of associated interpretations. Highlights: Isotopic analysis of Geloina erosa for radiocarbon and palaeoenvironmental data Complex interactions between environments and geochemistry of shell carbonates Stable isotopes from G. erosa difficult to interpret owing to complex environments Environmental and physiological factors negatively impact radiocarbon dating